If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 6(7) = 6x Multiply 6 * 7 x + 42 = 6x Reorder the terms: 42 + x = 6x Solving 42 + x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 42 + x + -6x = 6x + -6x Combine like terms: x + -6x = -5x 42 + -5x = 6x + -6x Combine like terms: 6x + -6x = 0 42 + -5x = 0 Add '-42' to each side of the equation. 42 + -42 + -5x = 0 + -42 Combine like terms: 42 + -42 = 0 0 + -5x = 0 + -42 -5x = 0 + -42 Combine like terms: 0 + -42 = -42 -5x = -42 Divide each side by '-5'. x = 8.4 Simplifying x = 8.4
| 3y=0+6 | | 2x-8=3x+3-13 | | 4p-2(p+1)= | | 60=5-11y | | 4x^3-32=0 | | 6(x-5)=4(x+2) | | -3x+6+x=14 | | -1.2=-0.8u+0.4u | | 3(3r-2)=5r+14 | | -4b+12=b^2 | | -1.2=-0.6u+0.4u | | -25+19=-8x+10x | | 6+2c=15 | | 5x-8=62 | | -5+.5x=-4 | | 6x-61=3x-13 | | 3b-8b= | | 6=4x-2 | | 2x+14=5x-35 | | 73=8x-7 | | 17-2x-3=-x+10 | | 126-7x=38x+16 | | 15d+5=7d+77 | | 12x+5=8x+33 | | 132-6x=3x+24 | | 6(x-1)=1.2 | | 7(a+2)=43.4 | | 10=6c-2 | | 5x-2=-17 | | 9e-7=20 | | 3v-8=-26 | | 2(w-1)+4=4(w-1) |